Analysis of spatio-temporal patterns of vegetation carbon use efficiency in watershed ecosystem and construction of ecological network: a case study of the Yangtze River Basin - Jikai Zhao; Qiang Yu; Chenglong Xu; Jun Ma; Fei Wang (GIScience & Remote Sensing)
Watershed ecosystems play a crucial role in the global carbon cycle, and the feedback effects of carbon cycling will have significant implications for future climate change. Therefore, this study utilizes MODIS data to estimate the vegetation carbon use efficiency (CUE) of the Yangtze River Basin (hereafter referred to as the YRB) aiming to explore its spatiotemporal patterns. Additionally, partial correlation analysis is employed to investigate the driving forces of climate and ecosystem types on vegetation CUE. Furthermore, an ecological network is constructed to examine the impact of CUE changes on the stability of the ecosystems.The results indicate that the CUE values in the vegetation ecosystems of the YRB exceed the threshold of 0.5, a constant CUE value commonly used in numerous ecological models. However, even within the same geographical region, different ecosystem types exhibit distinct CUE values, underscoring the complexity of the ecological landscape.Over the past 15 years, there has been an observable declining trend in CUE for the vegetation ecosystems within the YRB. Moreover, future projections suggest a continued decrease in CUE at the pixel scale, with land use changes possibly serving as a primary contributing factor. Interestingly, within the same ecosystem, higher temperatures and reduced precipitation appear to enhance CUE, implying that under adverse environmental conditions, plants may enhance their efficiency in converting atmospheric carbon into terrestrial biomass.Ultimately, an ecological network is established to investigate the influence of CUE changes on the stability of the ecosystems. Notably, alterations in CUE within the upstream ecological source areas of the Yangtze River exhibit a particularly pronounced impact on the overall ecosystem stability.These research findings hold paramount significance, deepening our understanding of carbon cycling variations in the YRB, while also providing valuable insights for safeguarding the ecological environment and formulating strategies to address the challenges posed by climate change.